Prospective evaluation of functional outcome in anterior cruciate ligament reconstruction with peroneus longus graft: a hospital-based study - Bosco, Dilip Stivart; Raj, Prunav Adhav Prithvi; Krishnan, Ponnilavan; Narayanan, Harinarayanan; Adisegaran, Anitha (International Journal of Research in Orthopaedics, 2025)
Background: Anterior cruciate ligament (ACL) reconstruction using the peroneus longus tendon (PLT) graft is emerging as a viable alternative to traditional autografts, offering comparable strength and reduced donor site morbidity. This study evaluates the functional outcomes and complications of ACL reconstruction using this PLT graft. Methods: A hospital-based prospective study was conducted on 50 patients with isolated ACL tears. Outcomes, including Lysholm, IKDC, Tegner activity, and modified Cincinnati scores, were assessed preoperatively and postoperatively at 6 and 12 months. Visual analog scale (VAS), range of motion (ROM), and complications were also recorded. Statistical significance was set at p<0.05. Results: Significant improvements were observed in Lysholm (46.2±10.3 to 89.4±6.7), IKDC (38.1±9.7 to 85.2±5.9), and modified Cincinnati (37.5±8.2 to 85.3±5.1) scores (p<0.001). ROM increased from 115°±15° to 140°±5°, and pain (VAS) decreased from 7.4±1.2 to 1.5±0.7. Complications were minimal, with a 2% graft failure rate and mild donor site morbidity. Conclusions: ACL reconstruction with the peroneus longus graft provides excellent functional outcomes and minimal complications, making it a reliable alternative to conventional autografts.